Um estudo variacionista e fonológico sobre o alçamento das vogais médias pretônicas na fala uberlandense - Felice, Ana Carolina Garcia Lima (2012)
In the present research we performed a descriptive analysis from the rising of the middle vowels pretonic with speakers from Uberlândia - MG. Following the variational method, we conducted interviews with the goal of seeking the vernacular speech of our informants. Thus, we compose a corpus with 5.199 words from the speech of 24 informants stratified by sex, age and education level, as established by GEFONO, group of studies in phonology, cooriented by Professor José Sueli de Magalhães . In addition to the extralinguistic factors used for the composition of research cells, we use linguistic factors, such as tonic vowel height, weight of pretonic syllabic, nasal / oral pretonic vowel; distance of pretonic vowel in relation to the stressed syllable, the pretonic syllable weight of the word, phonological preceding context: articulation point; preceding phonological context: continuity / non-continuity of the preceding consonant; following phonological context: articulation point; following phonological context: continuity / non continuity of following consonant. The data collected were passed through coding and run the program called GoldVarb. The factors considered relevant by the program, to the middle vowels pretonic rising were analyzed by us and then represented by geometry of features, phonological theory Autossegmental by Clements and Hume (1995). Our analysis was based on studies from Bisol (1981), Viegas (1987); Callou and Leite (1986); Callou, Leite and Coutinho (1991), Schwindt (2002), Silveira (2008); Cassique, Cruz, Dias and Oliveira (2009) and Wetzels (1992). At the end f this research, we conclude that the rising of the middle vowels occurs in Uberlândia and can be characterized by both aspects, neogrammarians where the rules of harmonizations applies and diffusionist when there is rising without apparent reason or cases that there is oscillation between rising form and not rising form.